Unlearning Cynicism: Rewriting Futures in Sustainability Education - Aragon-Guiller, Francisco; Raible, Stephanie (Tidsskrift for Social Innovation & Transformativ Entreprenørskabsdidaktik (SITE), 2026)
Sustainability educators increasingly encounter student attitudes of resignation and pessimism toward societal challenges, often manifesting as cynicism. Cynicism undermines agency, engagement, and motivation, constraining futures orientation and limiting constructive responses to complex problems. Distinct from skepticism, which supports critical thinking, cynicism discredits information and fosters disengagement, spreads within groups, and can escalate to burnout. This article examines the cultural and psychological roots of student cynicism, including its links to grief, frustration, mental health consequences, and highlights its detrimental effects on learning and agency. Pedagogical approaches, such as reflexive journaling, explicitly considering dark sides, and positive examples, serve to identify and confront cynicism to foster constructive engagement. By embracing critical thinking and healthy skepticism, sustainability education can help students recognize multiple futures, strengthen agency, and reframe attitudes toward social and environmental challenges, thereby supporting more agentic and empowered orientations to future-making.